High abundance of genus Prevotella is associated with dysregulation of IFN-I and T cell response in HIV-1-infected patients. (1st August 2020) - Pinacchio, Claudia; Scagnolari, Carolina; Iebba, Valerio; Santinelli, Letizia; Innocenti, Giuseppe P.; Frasca, Federica; Bitossi, Camilla; Scordio, Mirko; Oliveto, Giuseppe; Ceccarelli, Giancarlo; Antonelli, Guido; Mastroianni, Claudio Maria; et al.
Abstract : Objective: HIV-1-associated dysbiosis is most commonly characterized by overall decreased diversity, with abundance of the genus Prevotella, recently related to inflammatory responses. Design: A pilot study including 10 antiretroviral therapy-treated HIV-1-infected men and 50 uninfected controls was performed to identify the main gut dysbiosis determinants (e.g. Prevotella enrichment), that may affect mucosal antiviral defenses and T cell immunity in HIV-1-infected individuals. Methods: 16rRNA gene sequencing was applied to the HIV-1-infected individuals' fecal microbiota and compared with controls. Measurements of CD4 + and CD8 + T cell activation [CD38, human leukocyte antigen (HLA)-DR, CD38 HLA-DR] and frequencies of Th17, obtained from lamina propria lymphocytes isolated from five different intestinal sites, were performed by flow cytometry. IFNβ, IFNAR1 and MxA gene expression level was evaluated by real-time PCR in lamina propria lymphocytes. Nonparametric t tests were used for statistical analysis. Results: HIV-1-infected men had a significant fecal microbial communities' imbalance, including different levels of genera Faecalibacterium, Prevotella, Alistipes and Bacteroides, compared with controls. Notably, Prevotella abundance positively correlated with frequencies of CD4 + T cells expressing CD38 or HLA-DR and coexpressing CD38 and HLA-DR ( P  < 0.05 for all these measures). The same trend was observed for the activated CD8 + T cells. Moreover, Prevotella levels were inversely correlated with IFN-I genes ( P  < 0.05 for IFNβ, IFNAR1 and MxA genes) and the frequencies of Th17 cells ( P  < 0.05). By contrast, no statistically significant correlations were observed for the remaining bacterial genera. Conclusion: Our findings suggest that Prevotella enrichment might affect gut mucosal IFN-I pathways and T cell response in HIV-1-infected patients, thus contributing to immune dysfunction.